PEMBELAJARAN KOOPERATIF TIPE STUDENT ACHIEVEMENT DIVISIONS (STAD) - Gst Ag Sri Kerti (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2017)
This study is a classroom action research (PTK) with a research subject of 30 people, consisting of 18 men and 12 women. After data was collected, it was analyzed with quantitative descriptive analysis. The results of data analysis show can achieve good learning achievement of the application of STAD type cooperative learning model can improve student learning outcomes of class X P IBB 2 SMA Negeri 1 Ubud in Hindu education semester I year of lesson 2014/2015. This is evidenced by the increase in the average data of the student learning outcomes from cycle I to cycle II. Second, the application of STAD type cooperative learning model can accommodate the increase of student’s satisfaction level in learning. The level of satisfaction is represented by the response to the application of STAD type of cooperativelearning model. This is evidenced by the increase in the average data response of students fromcycle I to cycle II.